Synthesis, electrochemical and cytotoxic studies of bidentate dithiocarbazate Schiff bases and their metal (Ni, Cu,and Zn) complexes - Ramli, Syahirah (2016)
Three series of dithiocarbazate Schiff bases derived from S-2- methylbenzyldithiocarbazate, S-3-methylbenzyldithiocarbazate and S-4- methylbenzyldithiocarbazate were synthesised using thiophene-2-carboxaldehyde, methyl-2-thienylketone, 3-methylthiophene-2-carboxaldehyde, and 5- methylthiophene-2-carboxaldehyde via condensation. The Schiff bases were then complexed with respective metal salts to produce transition metal complexes. The metal complexes formed are expected to have general formula of [M(NS)2], [M(NS)2.H2O], [M(NS)2.2H2O],and [M(NS)(H2O)(OAc-)] where M = Cu2+, Ni2+, dan Zn2+.These compounds were characterised by elemental analysis, molar conductivity, magnetic susceptibility and various spectroscopy techniques including Fourier-Transform Infrared (FT-IR), Nuclear Magnetic Resonance (NMR), Mass Spectroscopy (MS), UltraViolet/Visible (UV/Vis) and Inductively Coupled Plasma- Atomic Emission Spectroscopy(ICP-AES) analyses. The elemental data obtained are in good agreement with the proposed molecular formula of the Schiff bases and metal complexes. The magnetic susceptibility measurements and spectral results support the coordination geometry in which the Schiff bases behave as bidentate NS donor ligand coordinating via azomethine nitrogen and thiolo sulphur atom. The Schiff bases and metal complexes have been evaluated for their biological activities against two bladder cancer cell lines, RT-112 (non invasive) and EJ-28 (invasive). Only [Cu(S2T2C)(H2O)(OAc-)], [Cu(S2M2TK)2], [Cu(S4T2C)2], [Cu(S4MB5MT)2] and[ Ni(S4M2TK)(H2O)(OAc-)] showed remarkable anticancer properties while the other compounds were inactive against both bladder cancer cell lines. A series of Schiff bases derived from S-4-methylbenzyldithiocarbazate were developed as self assembled monolayers (SAMs) and were tested for the detection of Zn2+ ion in water. All the Schiff base modified electrodes showed better response for the detection of Zn2+ion compared with the conventional electrode, indium tin oxide.